Optimalisasi Pengelolaan Sampah Melalui Gerakan Eco-Sport di SDN 75 Locok - Akmal; Maria Herlinda Dos Santos; Andi Ogo Darminto (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The waste problem in Indonesia is a critical issue that has an impact on health, biodiversity, and ecological sustainability. With waste generation reaching 431,085.22 tons in 2022, education about waste management is very important, especially in the school environment. The University of Muhammadiyah Bone Community Service Program (KKN) at SDN 75 Locok implements the Eco-Sport movement that integrates environmental education with sports activities. Through this approach, students not only learn about recycling and waste sorting, but also actively participate in maintaining a clean environment. The results showed increased environmental awareness, social skills, and creating a cleaner and healthier school environment. This movement has the potential to form a generation that cares about environmental issues.